Material composition and peptide sequence affects biomolecule affinity to and selectivity for h-boron nitride and graphene. Issue 62 (7th July 2020) - Brljak, Nermina; Parab, Atul D.; Rao, Rahul; Slocik, Joseph M.; Naik, Rajesh R.; Knecht, Marc R.; Walsh, Tiffany R.
Abstract : Pathways to nanosheet selective binding peptides are presented. Abstract : Nanosheet heterostructures offer emergent optical/electronic properties. These could be achieved using selective materials binding peptides, but lack of understanding of selectivity impedes advancement. Here we examine peptides with affinity for graphene or h-BN using quantitative experiments and molecular simulation to identify traits for design of 2D nanosheet selective peptides.